Effects of Sinensetin, Eupatilin, and Jaceosidin on Human Melanogenesis: A Pilot Study - Shilpi Goenka (Future Pharmacology)
Background/Objectives: Flavones, a class of plant-based flavonoids, have demonstrated conflicting anti-melanogenic activities in mouse and human melanocytes. Sinensetin (SNT), a polymethoxyflavone, has shown pro-melanogenic activity in B16F10 mouse melanoma (MM) cells, while eupatilin (EU) and jaceosidin (JAC), two flavones that are structural analogs of SNT, have not been evaluated for their effects on melanogenesis yet. Methods: Herein, the effects of SNT, EU, and JAC on melanogenesis in MNT-1 cells (human melanoma) and HEMn-DP cells (primary human melanocytes) have been examined. The mushroom tyrosinase (TYR) activity was tested in cell-free conditions, followed by examination of the cytotoxicity of the compounds via the Alamar Blue (AB) assay. Cellular melanin production and TYR activity were estimated in MNT-1 cells. The compounds were further examined in primary human melanocytes for melanin production, TYR activity, and protein levels. Results: Our findings show that SNT was a potent inhibitor of TYR activity in a cell-free assay, while EU and JAC had no effect. However, both SNT and EU were shown to exhibit anti-melanogenic activity (that was reversible) in human cells, while JAC was ineffective and cytotoxic. Conclusions: SNT and EU are potential novel candidates for hyperpigmentation treatment without cytotoxicity. Additional studies are warranted to elucidate the signaling mechanisms that govern their anti-melanogenesis action. Future research is necessary to assess the anti-melanogenic effectiveness of SNT/EU using 3D skin tissue equivalents and to select the optimal candidate.